KONFLIK SOSIAL PADA TOKOH UTAMA DALAM NOVEL I AM MALALA KARYA CHRISTINA LAMB - ANIS SETIYANTI (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2015)
Abstract: This study aims to reveal information about the forms, causes, and the completion of social conflicts described by the author in the novel